Effect of natural antimicrobials against Clostridium perfringens outgrowth during cooling of turkey breast - Peterson, Kristen Irene (Kansas State University, 2020)
The demand for natural, uncured processed meats has increased dramatically, resulting in the industry needing to find alternate ingredients to inhibit the outgrowth of Clostridium perfringens. The efficacy of natural antimicrobials to inhibit C. perfringens in processed meat products is not widely known. Two natural antimicrobials were evaluated in an uncured deli-style turkey breast product (1.5% salt) to determine inhibition of C. perfringens outgrowth during 15 h of chilling and to assess consumer acceptability. Four treatments of ground turkey breast were evaluated with the following formulations: control with no antimicrobials, 1.0% fruit/spice extract only, 1.0% dried vinegar only, and a combination of 1.0% fruit/spice extract and 1.0% dried vinegar. Treatments were inoculated with a three-strain mixture of C. perfringens spores to a targeted inoculation level of 2.0 log CFU/g. Individual 11 g portions were vacuum packaged, cooked to 71°C, and chilled from 54.4°C to 26.7°C in 5 h and from 26.7°C to 7.2°C in an additional 10 h. Triplicate samples were analyzed for growth of C. perfringens every 5 h by plating on tryptose-sulfite-cycloserine agar. A consumer panel (N=96) was also conducted to evaluate product for liking and acceptability. An interaction (P<0.05) between hour and treatment was observed for C. perfringens growth. The combination of fruit/spice extract and dried vinegar was found to be more effective (P<0.05) inhibiting outgrowth after 15 h than when these ingredients were used individually. Inclusion of antimicrobials did not affect (P>0.05) consumer ratings for liking. There were differences found (P<0.05) for consumer acceptability of flavor and flavor expectation, with the fruit/spice extract treatment being more acceptable to consumers than control. These results show that there is a synergistic effect against the outgrowth of C. perfringens when using both fruit/spice extract and dried vinegar together. It also shows that the use of either natural antimicrobial at these concentrations does not diminish the eating quality of the final product for consumers.
Keywords: Clostridium perfringens; Uncured; Turkey; Consumer panel